A voyage of discovery to the North Pacific Ocean, and round the world : in which the coast of north-west America has been carefully examined and accurately surveyed : Undertaken by His Majesty's command, principally with a view to ascertain the existence of any navigable communication between the North Pacific and North Atlantic Oceans, and performed in the years 1790, 1791, 1792, 1793, 1794, and 1795, in the Discovery sloop of war, and armed tender Chatham, under the command of Captain George Vancouver : in three volumes, Vol. I. - Vancouver, George, 1757-1798.; Guerra, Francisco, 1916- , ant. pos. BHI BH FG 2741.; Alexander, William, 1767-1816, il.; Heath, James, 1757-1834, il.; Landseer, John, 1769-1852, il.; Edwards, John, fl.1798, imp. (Londres); Robinson, John., fl.1781-1806, imp. (Londres); Robinson, Georges G., imp. (Londres); Vancouver, John, m.1828?, ed. lit. (London : printed for G.G. and J. Robinson . and J. Edwards, 1798)
Mode of access: Internet. Editado por John Vancouver según consta en la Advertencia del editor. En la relación de las láminas que figura en prelim., se indica que la lámina VII debe ir enfrentada con la p. 467, pero este tomo sólo llega hasta la 432. Los grabados calcográficos: I. A deserted indian village in King George III, Sound, New Holland (p. 54). II. Four remarkable, supported poles, in Port Townshend, Gulph of Georgia (p. 234). III. Mount Rainier, from the South part of Admiralty Inlet (p. 268). IV. Village of the Friendly Islands at the entrance fo Bute's Canal (p. 326). V. Cheslakee's village in Johnstone's Straits (p. 346). VI. The discovery on the Rocks in Queen Charlotte's Sound (p.364). VII. Friendly Cove, Nootka Sound (p. 388). Todas los grabados dibujados por W. Alexander y grabados por J. Heath y J. Landseer. Sign.: []3, a-d4, A-2Z4, 3A-3I4.